2009
DOI: 10.1093/carcin/bgp306
|View full text |Cite
|
Sign up to set email alerts
|

Transcription coactivator PBP/MED1-deficient hepatocytes are not susceptible to diethylnitrosamine-induced hepatocarcinogenesis in the mouse

Abstract: Nuclear receptor coactivator [peroxisome proliferator-activated receptor-binding protein (PBP)/mediator subunit 1 (MED1)] is a critical component of the mediator transcription complex. Disruption of this gene in the mouse results in embryonic lethality. Using the PBP/MED1 liver conditional null (PBP/MED1ΔLiv) mice, we reported that PBP/MED1 is essential for liver regeneration and the peroxisome proliferator-activated receptor α ligand Wy-14,643-induced receptor-mediated hepatocarcinogenesis. We now examined th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 50 publications
0
24
0
Order By: Relevance
“…[24][25][26][27][28] Histological studies reveal that the HCC expansion occurs in the backdrop of chronic inflammation and NF-κB is the chief mediator of inflammation, regulating other inflammatory molecules either downstream or upstream. 18,23,29 Liver is the production center for synthesis of cytokines such as TNF-α, IL-1β, and IL-6 by blood cells (monocytes and lymphocytes). Not only liver but also few other cells such as murine, kupffer cells, and human hepatocytes produce IL-1β, IL-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26][27][28] Histological studies reveal that the HCC expansion occurs in the backdrop of chronic inflammation and NF-κB is the chief mediator of inflammation, regulating other inflammatory molecules either downstream or upstream. 18,23,29 Liver is the production center for synthesis of cytokines such as TNF-α, IL-1β, and IL-6 by blood cells (monocytes and lymphocytes). Not only liver but also few other cells such as murine, kupffer cells, and human hepatocytes produce IL-1β, IL-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%
“…All tumors that arise in mice carrying a conditional liver PBP knockout develop from cells that have retained PBP expression. This indicates that PBP is required for the development of hepatocellular carcinoma in mice (Matsumoto et al 2010). Moreover, it has been shown that PBP is required for mammary gland development (Yuzhi Jia et al 2005).…”
Section: Treatment Of Her2/neu-positive Breast Cancermentioning
confidence: 92%
“…No proliferative expansion of PBP/MED1 null hepatocytes was noted in the PBP/MED1DLiv mouse livers. Multiple hepatocellular carcinomas developed in the DEN-initiated PBP/MED1fl/fl and PBP/MED1DLiv mice [67]. DEN may activate PDGFR /PIK3CA/Akt signaling through -Catenin, and mediate C/EBP phosphorylation through the ubiquitin-proteasome system (UPS), and regulate PBP/MED1, and involve nasopharyngeal carcinogenesis.…”
Section: Biomolecular and Signal Pathways Activated By Denmentioning
confidence: 99%